Imaging flowers: a guide to current microscopy and tomography techniques to study flower development. (8th May 2020) - Prunet, Nathanaël; Duncan, Keith
Abstract : We review modern light microscopy and computed projection tomography methods, their capabilities and limitations, and their current and potential applications to the study of flower development and fertilization. Abstract: Developmental biology relies heavily on our ability to generate three-dimensional images of live biological specimens through time, and to map gene expression and hormone response in these specimens as they undergo development. The last two decades have seen an explosion of new bioimaging technologies that have pushed the limits of spatial and temporal resolution and provided biologists with invaluable new tools. However, plant tissues are difficult to image, and no single technology fits all purposes; choosing between many bioimaging techniques is not trivial. Here, we review modern light microscopy and computed projection tomography methods, their capabilities and limitations, and we discuss their current and potential applications to the study of flower development and fertilization.